Performance Investigation of Topologically Optimized Manipulator Link - Kulkarni, Aditya; Javed, Arshad (Asian Journal of Engineering and Applied Technology, 2014)
Reducing weight of components in a manipulator is the need of robotic industry, not only to save cost by reducing the material but also to optimize the power consumption. Hence, topology optimization of manipulator links has wider scope to research and deliver the best possible solutions to design a system. The paper focus on investigating the performance of the link using topology optimization and dynamic modeling. In this work, topology optimization is utilized to generate optimum shape and size of link, finite element approach is adopted in finding the inertia of the given body, deflection with stress and followed by kinematic modeling. Further trajectory planning is done and Lagrange-Euler formulation is applied to find out required joint-torque values for each increment of motion.